PEMBELAJARAN BERBASIS TEKNOLOGI UNTUK MENINGKATKAN KETERLIBATAN MATEMATIKA SISWA PENYANDANG DISABILITAS DALAM PENDIDIKAN DASAR INKLUSIF: A SCOPING REVIEW - Basmalah, Mutiara; Widayanti, Costrie Ganes (Jurnal Muara Pendidikan, 2025)
Teaching mathematics in elementary school is crucial to provide basic foundation for understanding more complex math concepts.Teachers in inclusive schools frequently feel unqualified to teach mathematical concepts and operations to students with impairments or disability. In order to accommodate the various needs of pupils, Universal Design for Learning (UDL) places a strong emphasis on teaching mathematics using a technology-based approach. This study aims to map the many forms of technology and how they affect the learning of mathematics in inclusive elementary schools for students with disabilities.This study used the PRISMA-ScR protocol. A comprehensive search was conducted using the Scopus and Google Scholar databases. The review of four articles that met the inclusive criteria found that the use of multimedia gamification, interactive games (smart apps creator), visual scratch, and SPECOMATSO supported students with disabilities’ understanding of mathematical concepts, encouraged active participation and learning motivation, also strengthened communication, social, and digital literacy skills of students with disabilities. This study offers insight into the development of mathematics learning media in inclusive elementary schools.